Trichogramma chilotraeae PARASITOID TELUR Helicoverpa armigera (Hubner) PADA POPULASI INANG RENDAH - - Sujak; - Nurindah (Agrovigor, 2011)
Helicoverpa armigera Hubner is an insect pest of corn and cotton crops. Eggs are laid by  H. armigera imago on corn silk and cotton crops often have high mortality, mainly caused by egg parasitoid. H. armigera egg on various agroecosystem reported can  be parasited by at least 12 species of  Trichogrammatidae. The purpose of this study was to determine the diversity of  Trichogrammatidae family as  parasitoid eggs of  H. armigera on  low population. H. armigera egg sample taken from Asembagus, Lamongan and Blora at 1 m2 field  both monoculture and intercropping. Observation of parasitoids and predators  done at the Laboratory of Biological Control Balittas Malang. Parasitoid that appears preserved in the Hoyer medium for identification purposes. low population of  H. armigera Egg in Asembagus is  4 eggs/m2 in both monoculture maize and intercropping with 86-100 days after transplanting (DAT) cotton and  4.5 egg/m2 on cotton monoculture and intercropping with 75  DAT soybean, while 2 eggs/m2 in the Lamongan and Blora corn agroecosystem. The dominant egg parasitoid in Asembagus is T. chilotraea, as well as in Lamongan and Blora.